Age and Perceived Employability as Moderators of Job Insecurity and Job Satisfaction: A Moderated Moderation Model - Yeves, Jesus; Bargsted, Mariana; Cortes, Lorna; Merino, Cristobal; Cavada, Gabriela (Frontiers in Psychology, 2019)
Workforce ageing and the need to work longer implies several challenges worldwide. Due to the potential for career prolongation, one such implication is to understand how age and perceived employability buffers relationship effects between job insecurity and job satisfaction. Therefore, this research aims to investigate the moderating roles of perceived employability and age on the relationship between job insecurity and job satisfaction. Hypotheses were tested using a three-way interaction model based on a cross-sectional design with a representative sample of 1,116 Chilean workers. Results show that age plays an important role in employees with high perceived employability; however, it has no effect on employees with low perceived employability. Younger workers with high perceived employability suffer less than do older employees with high perceived employability in terms of intrinsic job satisfaction. From a theoretical point of view, perceived employability in older workers does not reduce the unfavorable consequences of job insecurity. Regarding practical implications, organizations should manage and develop older workers by focusing on intrinsic aspects of their careers and on retirement preparation, as this will improve control and other positive resources in this population.